Personal Ornaments and Burial Rites in Prehistory - Selena Vitezović (Etnoantropološki Problemi)
Archaeological burial contexts are among particularly attractive topics for both experts – archaeologists, and wider audiences. The reasons behind this are partially the rich, attractive portable finds that are usually associated with these contexts, but also the interpretative potential, i.e., insight into rituals and symbolic values of people in the past.